A la recherche des paramètres de l’élaboration du sens au sein des énoncés - Sarah De Vogüé (Corela)
This paper discusses the principles of predictivity and falsifiability applied to semantic analysis and proposes an inductive approach based on parameters involved in the unfolding of meaning. It claims that linguistic meaning emerges out of ‘enunciative’ elaborations at every level of linguistic analysis. These elaborations proceed from unlimited development, induced by four sources of diversification: syntagms, paradigms, reformulations and paraphrases. A characterization of the utterance (seen as the French “énoncé”) is proposed here, based on the articulation between the reference to be and the referential value it elaborates. Some parameters involved in the construction of meaning are discussed: what is described as “schematic forms” characterizing the identity of any lexical unity, but also the different modalities of articulation between referent and referential value, as well as inter-subjective positioning processes, which are bound to be involved in any construction of identity.